2012
DOI: 10.1007/s10896-012-9445-1
|View full text |Cite
|
Sign up to set email alerts
|

Family Closeness and Domestic Abuse Among Caribbean and South American Women in South Florida

Abstract: This paper focuses on the importance of family member closeness as a protective factor against domestic abuse. We explore the link between long-lasting relations within the family and intrafamilial violence perpetrated against women in Latino households in South Florida. We use data from an Inter-generational Transmission of Drug Use between Latina Mothers and Daughters (ITDMD) study. The study includes data on family relations and domestic abuse. We estimate a series of multivariate regressions to obtain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Because illicit substance and alcohol use and emotional abuse are both prevalent in Latinos, [12] it is important to study if Latina women suffer additional abuse by other Latino family members and their co-workers, friends, or acquaintances. In this context, the aims of this study were to determine: (AIM 1) whether the proportion of women who reported being emotionally abused at Wave 2 but who did not report any emotional abuse during Wave 1 varies between older and younger Latinas; (AIM 2) who are the perpetrators of emotional abuse against adult and older Latinas; (AIM 3) whether women are emotionally abused by different social actors during the same period of time; and (AIM 4) whether illicit substance abuse and heavy alcohol use are significantly associated with emotional abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Because illicit substance and alcohol use and emotional abuse are both prevalent in Latinos, [12] it is important to study if Latina women suffer additional abuse by other Latino family members and their co-workers, friends, or acquaintances. In this context, the aims of this study were to determine: (AIM 1) whether the proportion of women who reported being emotionally abused at Wave 2 but who did not report any emotional abuse during Wave 1 varies between older and younger Latinas; (AIM 2) who are the perpetrators of emotional abuse against adult and older Latinas; (AIM 3) whether women are emotionally abused by different social actors during the same period of time; and (AIM 4) whether illicit substance abuse and heavy alcohol use are significantly associated with emotional abuse.…”
Section: Introductionmentioning
confidence: 99%
“…A study focusing on the links between family relationships and emotional abuse in Latino families underscored the importance of the mother in her children's lives, including throughout adulthood (14). Compared to other aging populations, Latinos are twice as likely to live with family members and foreign born Latinos are especially dependent on their children (15); nonetheless, Latino parents are still expected to be an authority figure to their children (16).…”
Section: Introductionmentioning
confidence: 99%
“…Family violence itself is defined as 'a spectrum of harmful acts within families that are beyond normally accepted family dynamics which encompasses sibling violence, elder abuse, child maltreatment, dating violence, and Intimate Partner Violence' [Smith and Ireland 2009: 493]. Intimate Partner Violence is a domestic form of abuse which is a forceful tactic, intentionally employed by family members to cause physical and /or psychological harm to the victim [Aysa-Lastra, Rojas ,Dillon, Duan and Rosa 2012]. This violence occurs in all countries and socioeconomic groups; however, its prevalence and manifestations vary widely [Tartakovsky and Mezhibovsky, 2012] our knowledge on the causes of this social problem.…”
Section: Introductionmentioning
confidence: 99%